FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KESEMBUHAN CIDERA PADA TULANG AKIBAT BENCANA - Sri Sulastri (Jurnal Ilmiah Cerebral Medika, 2019)
The purpose of this study was to determine the Factors That Influence The Level Of Healing In Injury Bone. This research uses descriptive correlation design with cross sectional approach. This research was conducted at the Dr.Reksodiwiriyo Padang Hospital with 30 people who had long fractures and were selected based on inclusion criteria. The measuring instrument is a questionnaire that has been tested for validity and reliability. The analysis used was univariate and bivariate using the Chi Square test. The results of this study indicate that there is a significant relationship between socioeconomic status (p value = 0.049) with patient anxiety, and there is no significant relationship between nursing services (p value = 0.440), level of knowledge (p value = 0.024), family support (p value = 0.127) with patient anxiety. The results of this study recommend that hospitals improve psychosocial nursing care and help direct the mechanism of adaptive treatment to patients treated at the hospital thereby reducing anxiety.